2008
DOI: 10.1074/jbc.m703910200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Enzymatic Activity of the Actin Cross-linking Domain from the Vibrio cholerae MARTX Toxin

Abstract: Vibrio cholerae is a Gram-negative bacterial pathogen that exports enterotoxins, which alter host cells through a number of mechanisms resulting in diarrheal disease. Among the secreted toxins is the multifunctional, autoprocessing RTX toxin (MARTX Vc ), which disrupts actin cytoskeleton by covalently cross-linking actin monomers into oligomers. The region of the toxin responsible for cross-linking activity is the actin cross-linking domain (ACD). In this study, we demonstrate unambiguously that ACD utilizes G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 48 publications
3
39
0
Order By: Relevance
“…Both loops are distant from the actin binding sites of major G-actin binding proteins, such as thymosin ␤4 and profilin. This correlates with our recent findings that both proteins do not inhibit actin cross-linking by ACD (10). Both loops are mobile, unstructured, and protrude out of the body of the actin molecule, making them good substrates for enzymes.…”
Section: Acd-induced Cross-linking Precludes Actin Polymerization Intsupporting
confidence: 78%
See 2 more Smart Citations
“…Both loops are distant from the actin binding sites of major G-actin binding proteins, such as thymosin ␤4 and profilin. This correlates with our recent findings that both proteins do not inhibit actin cross-linking by ACD (10). Both loops are mobile, unstructured, and protrude out of the body of the actin molecule, making them good substrates for enzymes.…”
Section: Acd-induced Cross-linking Precludes Actin Polymerization Intsupporting
confidence: 78%
“…To reveal the mechanism of actin cross-linking by ACD, we limited the extent of the cross-linking to yield mainly dimers (10). We then used limited proteolysis of purified ACD cross-linked actin dimers and uncross-linked monomers to identify the actin peptides that are covalently linked.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, purified MARTX effectors tend, in general, to behave poorly in solution, as they seem to be evolutionarily selected to be unstable, likely because of a need to unfold easily for type I secretion out of the bacterium and again for translocation into the eukaryotic cell cytosol. ACD and CPD are both known to require cofactors (50,51), and for the CPD, it has been demonstrated that the recombinant protein does not become stably folded in vitro until it associates with its activator (52). Thus, it is possible that VvExoY does require a cofactor that would increase both its in vitro stability and its activity.…”
Section: Discussionmentioning
confidence: 99%
“…The RhoGTPase-inactivation domain (RID) causes conversion of activated GTP-bound Rho, Rac, and CDC42 to the inactive GDP-bound forms resulting in depolymerization of actin (10). The adjacent actin cross-linking domain (ACD) catalyzes the covalent cross-linking of monomeric G-actin resulting in the irreversible destruction of the cytoskeleton (7,11,12). Together these domains rapidly round eukaryotic cells without causing cell lysis.…”
mentioning
confidence: 99%